No sweat: managing menopausal symptoms at work - Martha Hickey; Kathleen Riach; Reza Kachouie; Gavin Jack (Journal of Psychosomatic Obstetrics and Gynecology, 2017)
Introduction: Menopause usually occurs between the ages of 45 and 55, a time when women are likely to be in the paid workforce. Most women have menopausal symptoms and these may impact on daytime function and work performance. This study examines the relationship between reproductive stage, menopausal symptoms and work, and advises how employers can best support menopausal women. Methods: An online and paper-based survey was completed in 2015–16 by 1092 women (22% response rate) aged 40 years plus employed in three hospitals in metropolitan Australia. Survey questions examined demographics, health and lifestyle variables, menopausal symptom reporting, and work-related variables. Reproductive stage was determined using modified STRAW +10 principal and descriptive criteria. Results: Reproductive stage was not significantly associated with work engagement, organizational commitment, job satisfaction, work limitations and perceived supervisor support. Postmenopausal women had lower intention to leave their organizations than pre- and peri-menopausal women. While sleep problems were the most commonly reported menopausal symptom by peri-menopausal women, for postmenopausal women it was joint and muscular discomfort. Only hot flushes and vaginal dryness were significantly more frequent in peri- and post, compared to pre-menopausal women. In general, women rated their work performance as high and did not feel that menopausal symptoms impaired their work ability. Most women would appreciate greater organizational support, specifically temperature control, flexible work hours and information about menopause for employees and managers. Discussion: Most women did not believe that menopausal symptoms negatively impacted on their work. Organizational changes may reduce the burden of menopausal symptoms in the workplace